Toxic Effects of the Most Common Components of Energetic Co-Crystals - Xinying Peng; Cunzhi Li; Huan Li; Hui Deng; Xiaoqiang Lv; Ting Gao; Jiachen Shen; Bin Zhao; Zhiyong Liu; Junhong Gao (Molecules)
Hexanitrohexaazaisowurtzitane (CL-20) is a high-energy-density material known for its exceptional explosive performance, but it suffers from significant safety concerns due to its high sensitivity. To mitigate this issue, researchers have explored the synthesis of CL-20-based cocrystals with other energetic materials to achieve a balance between energy output and safety. Recent advancements in CL-20 cocrystals have focused on developing novel synthesis methods and leveraging computational design techniques to predict and optimize their physicochemical properties. However, the toxicity of CL-20 cocrystals, along with their environmental and health risks, remains a critical concern. This review systematically examines recent progress in CL-20 cocrystal energetic materials, emphasizing toxicity profiles and mechanistic insights into their components. The findings serve as a foundation for the development of safer energetic materials, thereby facilitating sustainable advancements in manufacturing technologies and industrial applications of CL-20.